Versions of Transformation: Insights On Good Local Governance In Low-Income Cities In The Philippines - Cruz Manzano, Soleil Erika (Indonesian Association for Public Administration, 2025)
The economic status of a local government is not a determinant of its governance quality. In the case of Philippine cities, the Seal of Good Local Governance (SGLG) award conferment demonstrates that good institutional performance is achievable regardless of income classification. Annually, awards come from the entire income class spectrum, from the highly urbanized city to the poorest, albeit inconsistently. This study examines the factors found in low-income cities that perform well, despite resource limitations. Using the cases of the cities of Balanga and Lamitan – consistent SGLG awardees – this qualitative study suggests that sociocultural factors (e.g., social networks), rather than socioeconomic factors (e.g., income), influence local government performance. As seen in its dense social networks, a city's stock of social capital manifests as active civic participation that reinforces good institutional performance. Similarly, local chief executives with substantial social capital influence good governance and have potential to become local policy entrepreneurs. They thrive in low-income cities due to the networks and resources that allow them to innovate. The results of this study emphasize the importance of civic participation in improving the institutional performance of local governments.